2011
DOI: 10.2486/indhealth.ms1058
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Expression of 8-Nitroguanine in the Brain of Mice Exposed to Arsenic Subchronically

Abstract: Arsenic (As) is a well-known carcinogen and a notorious health killer on the earth. The regional As toxicosis is becoming a global problem of public health. An anthropogenic source of arsenic exposure stems from the widespread use of arsenical drugs in food-animal production in the United States and China. This use results in residual contamination of food products from animals raised with the drugs, as well as environmental contamination associated with disposal of wastes from these animals 1) . Chronic expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
(27 reference statements)
0
6
0
Order By: Relevance
“…targets of arsenic neurotoxicity and show myelin damage, disappearance of axons, vacuolar degeneration, and loss of cell-cell junction (Ma et al, 2010;Piao et al, 2011;Zarazua et al, 2010). Arsenic has been found to cause cholinergic dysfunctions associated with decreased activity of brain acetylcholinesterase and impaired learning and memory in experimental studies (Flora et al, 2009;Kopf et al, 2001;Nagaraja and Desiraju, 1994;Rodriguez et al, 2001;Wang et al, 2007).…”
Section: A C C E P T E D Mmentioning
confidence: 99%
“…targets of arsenic neurotoxicity and show myelin damage, disappearance of axons, vacuolar degeneration, and loss of cell-cell junction (Ma et al, 2010;Piao et al, 2011;Zarazua et al, 2010). Arsenic has been found to cause cholinergic dysfunctions associated with decreased activity of brain acetylcholinesterase and impaired learning and memory in experimental studies (Flora et al, 2009;Kopf et al, 2001;Nagaraja and Desiraju, 1994;Rodriguez et al, 2001;Wang et al, 2007).…”
Section: A C C E P T E D Mmentioning
confidence: 99%
“…Recent animal studies suggest that neurons in the brain may be the major targets of arsenic neurotoxicity and show myelin damage, disappearance of axons, vacuolar degeneration, and loss of cell-cell junction. Arsenic exposure from drinking water containing 1-2 mg/L (approximately 0.1–0.2 mg/kg/day) has been shown to induce oxidative DNA damage in the brain [710]. While inorganic arsenic exposure has been correlated with impairments of new learning and recent memory, few studies have explored its effects on mood disorder such as anxiety and depression.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies showed that arsenic exposure produced hippocampal ultrastructural changes, down-regulation of NMDA receptor and postsynaptic signaling ( Luo et al 2012 ), and inhibited hippocampal neurogenesis ( Liu et al 2012 ). Arsenic also modulated DNA methylation and contributed to neural tube defects via epigenetic mechanisms ( Han et al 2011 ), promoted nitrative DNA lesions ( Piao et al 2011 ), and down-regulated mitochondrial succinate dehydrogenase subunit A ( Hong et al 2009 ) and Camk4 ( Wang et al 2009 ). Neuroglobin (Ngb) had a protective role in the cerebellum against arsenite-induced oxidative stress ( Wang J et al 2012 ).…”
Section: Resultsmentioning
confidence: 99%